2018
DOI: 10.1021/acssuschemeng.8b00102
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Aluminum Catalysts for the Chemical Fixation of Carbon Dioxide into Cyclic Carbonates

Abstract: Bifunctional aluminum complexes supported by novel zwitterionic NNO-donor scorpionate ligands were found to be efficient bifunctional catalysts for cyclic carbonate synthesis from terminal and internal epoxides in good yields and with broad substrate scope. Neutral scorpionate ligands (1–2) were designed and used as precursors to obtain two novel zwitterionic NNO-heteroscorpionate ligands (3–4). Reaction of 3 or 4 with [AlX3] (X = Me, Et) in a 1:1 or 1:2 molar ratio afforded the mononuclear and dinuclear catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 87 publications
4
51
0
Order By: Relevance
“…Deuterated solvents were stored over activated 4 Å molecular sieves and degassed by several freeze-thaw cycles. The synthesis of ligand precursors and zinc complexes was carried out as previously reported [53][54][55]. Cyclohexene oxide (Sigma-Aldrich, Munich, Germany) was pre-dried over calcium hydride, distilled under vacuum and stored under nitrogen in a glove box.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…Deuterated solvents were stored over activated 4 Å molecular sieves and degassed by several freeze-thaw cycles. The synthesis of ligand precursors and zinc complexes was carried out as previously reported [53][54][55]. Cyclohexene oxide (Sigma-Aldrich, Munich, Germany) was pre-dried over calcium hydride, distilled under vacuum and stored under nitrogen in a glove box.…”
Section: Materials and Reagentsmentioning
confidence: 99%
“…In the closely related investigation, the same research team showed that performing the process in the presence of 5 mol% of aluminum-based complex 31 as a catalyst and without any cocatalyst at 35 C afforded the expected carbonates 33 in high to excellent yields (Scheme 19). 55…”
Section: Aluminummentioning
confidence: 99%
“…Additionally, we have previously reported the use of heteroscorpionate metal complexes as efficient catalysts for cyclic carbonate formation [11i,18] . For instance, single‐component aluminum catalysts have shown to be efficient catalysts for the preparation of various cyclic carbonates using a low catalyst loading (0.25–2.50 mol %) under relatively mild reaction conditions (70–90 °C and 10 bar pressure) [18b,c] . Recently, we have focused our interest towards the employment of waste‐derived starting materials for the preparation of bio‐based cyclic carbonates derived from terpenes and furan derivatives [11i] .…”
Section: Introductionmentioning
confidence: 99%